2020
DOI: 10.3390/ijerph17249321
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Self-Perceived Barriers and Enablers toward Adopting a Mediterranean Diet in Australia: An Application of the Theory of Planned Behaviour Framework

Abstract: The transferability of a Mediterranean diet (MedDiet) in non-Mediterranean populations is appealing. However, little is known about the perceived enablers or barriers toward adherence, particularly in Australia. This study aimed to investigate the perceived beliefs, barriers, and enablers toward adherence to a MedDiet in Australian adults. Barriers and enablers were assessed using a self-administered online questionnaire, which included questions aligned with the Theory of Planned Behaviour (TPB). The survey w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 80 publications
3
51
1
Order By: Relevance
“…This research failed to introduce discrete emotions as mediators in analyzing the interactions between framing effects and intentions. Although the research fully measured and investigated people’s health beliefs, people’s emotions, including fear, sadness, guilt, and relief, can also lead to different behavioral responses [ 30 , 62 , 65 , 66 , 67 , 68 , 69 , 70 ]. Future research may seek to examine the mediating roles of emotions on framing effects, especially the mediating role of fear.…”
Section: Discussionmentioning
confidence: 99%
“…This research failed to introduce discrete emotions as mediators in analyzing the interactions between framing effects and intentions. Although the research fully measured and investigated people’s health beliefs, people’s emotions, including fear, sadness, guilt, and relief, can also lead to different behavioral responses [ 30 , 62 , 65 , 66 , 67 , 68 , 69 , 70 ]. Future research may seek to examine the mediating roles of emotions on framing effects, especially the mediating role of fear.…”
Section: Discussionmentioning
confidence: 99%
“…In an Australian study where self-perceived barriers toward adopting MD were assessed, it was shown that behavioral control and perceived health benefits for diet quality improvement were the most prominent positive influencing factors to follow a MD. Meanwhile, dietary adherence was identified as a negative factor [82]. In a cross-sectional study in the United States, convenience, sensory factors, and health were more significant barriers for adherence to the MD in states where the incidence of stroke is higher, but not in other states [83].…”
Section: Mediterranean Diet In the Elderlymentioning
confidence: 99%
“…In this regard, Scannell et al [ 19 ] analyze, in their article in this Special Issue, the eventual transferability of the Mediterranean diet to non-Mediterranean populations such as Australia, exposing the difficulties in transplanting a foreign model to a society with different dietary patterns. They state that the perceived health benefits and improved diet quality are identified as major advantages to this eventual adoption.…”
Section: Scope Of This Special Issuementioning
confidence: 99%